Gestão da qualidade na construção civil - Jesus, Daiane Matias de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Quality Management has become an essential requirement for all companies intending to compete and ensure its place in the labor market. Several tools have been created as a way of ensuring the effectiveness of quality management, in order to control and manage the quality of services and products to ensure a final product with a high degree of competition and quality, besides satisfaction and exceeding customer expectations. Due to the great importance it has at the presente time on the world stage and internationally, civil construction felt the need to eliminate the defects and the lack of quality that have become so common over time to ensure a quality product and it´s customers satisfaction. It was then that this industry began to implement and develop more modern techniques and tools for quality control in construction. Quality achieved position in global market, defining which companies would continue and which companies would leave it, not to mention it became insistently required by the customer. Some tools such as ISO 9000 guided companies seeking a quality management. This presentation will present some of these management tools and their applicability in the civil construction industry. Thus, it will be evident that despite the current resources it is necessary that civil construction professionals abandon the idea that considers quality management a problem and begin thinking about it as a solution to prevent future errors and ensure the quality of their services

A Gestão da Qualidade tornou-se um requisito indispensável para todas as empresas que pretendem competir e garantir seu espaço no mercado de trabalho. Com a finalidade de controlar e gerenciar a qualidade dos serviços e produtos garantindo um produto final com elevado grau de concorrência e qualidade, além da satisfação e superação das expectativas do cliente final, várias ferramentas foram criadas como forma de assegurar a eficiência da gestão da qualidade. Devido à grande importância que tem hoje no cenário mundial e internacional, a Construção Civil sentiu a necessidade de eliminar os defeitos e à falta de qualidade que se tornaram tão comum com o tempo a fim de garantir um produto de qualidade e a satisfação do seu cliente. Foi então que este setor passou a implementar e desenvolver cada vez mais técnicas e ferramentas modernas para o controle da qualidade na Construção. A qualidade conquistou espaço no mercado globalizado definindo quais empresas continuam e quais saem dele, além de que passou a ser exigida de forma insistente pelo cliente. Algumas ferramentas como a ISO 9000:2000 orientam as empresas que buscam uma gestão de qualidade. No presente trabalho serão apresentadas algumas destas ferramentas de gestão e sua aplicabilidade no setor da Construção Civil. Desta forma, ficará evidente que apesar dos recursos existentes é necessário que os profissionais da Construção deixem de encarar a gestão da qualidade como um problema passando a considerá-la como solução para prevenir futuros erros e garantir a qualidade de seus serviços
Keywords: Gestão da qualidade total; Construção civil; Controle de processo; Quality management